Plasmodium knowlesi in pig-tailed macaques: a potential new model for malaria vaccine research - Melanie J. Shears; Rebekah A. Reynolds; Caroline J. Duncombe; Felicia N. Watson; Weston J. Staubus; Chris Chavtur; Annette M. Seilie; Tuan M. Tran; Sumana Chakravarty; Stephen L. Hoffman; Sean C. Murphy (Malaria Journal, 2023)
Abstract Background Plasmodium knowlesi is an established experimental model for basic and pre-clinical malaria vaccine research. Historically, rhesus macaques have been the most common host for malaria vaccine studies with P. knowlesi parasites. However, rhesus are not natural hosts for P. knowlesi, and there is interest in identifying alternative hosts for vaccine research. The study team previously reported that pig-tailed macaques (PTM), a natural host for P. knowlesi, could be challenged with cryopreserved P. knowlesi sporozoites (PkSPZ), with time to blood stage infection equivalent to in rhesus. Here, additional exploratory studies were performed to evaluate PTM as potential hosts for malaria vaccine studies. The aim was to further characterize the parasitological and veterinary health outcomes after PkSPZ challenge in this macaque species. Methods Malaria-naïve PTM were intravenously challenged with 2.5 × 103 PkSPZ and monitored for blood stage infection by Plasmodium 18S rRNA RT-PCR and thin blood smears. Disease signs were evaluated by daily observations, complete blood counts, serum chemistry tests, and veterinary examinations. After anti-malarial drug treatment, a subset of animals was re-challenged and monitored as above. Whole blood gene expression analysis was performed on selected animals to assess host response to infection. Results In naïve animals, the kinetics of P. knowlesi blood stage replication was reproducible, with parasite burden rising linearly during an initial acute phase of infection from 6 to 11 days post-challenge, before plateauing and transitioning into a chronic low-grade infection. After re-challenge, infections were again reproducible, but with lower blood stage parasite densities. Clinical signs of disease were absent or mild and anti-malarial treatment was not needed until the pre-defined study day. Whole blood gene expression analysis identified immunological changes associated with acute and chronic phases of infection, and further differences between initial challenge versus re-challenge. Conclusions The ability to challenge PTM with PkSPZ and achieve reliable blood stage infections indicate this model has significant potential for malaria vaccine studies. Blood stage P. knowlesi infection in PTM is characterized by low parasite burdens and a benign disease course, in contrast with the virulent P. knowlesi disease course commonly reported in rhesus macaques. These findings identify new opportunities for malaria vaccine research using this natural host-parasite combination. Graphical Abstract